2012
DOI: 10.1074/jbc.m111.260349
|View full text |Cite
|
Sign up to set email alerts
|

Regenerating Islet-derived 1α (Reg-1α) Protein Is New Neuronal Secreted Factor That Stimulates Neurite Outgrowth via Exostosin Tumor-like 3 (EXTL3) Receptor

Abstract: Background: Reg-1␣ is a small secretory protein overexpressed during the early stages of Alzheimer disease. Results: Secreted Reg-1␣ stimulates axon outgrowth, and this paracrine effect is mediated by its receptor EXTL3. Conclusion: Reg-1␣ emerges as an important actor in brain plasticity and the regenerative process. Significance: Learning how Reg-1␣ regulates the nerve cells is important for understanding its implications in early stages of Alzheimer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
4
25
0
Order By: Relevance
“…A Manhattan plot for the two tailed tests is shown in Figure 1, and the top 20 results are displayed in Table 2. The most significant result emerged for a variant on chromosome 2 (rs879022, bp 79364463, p = 4.72e-09) located in a cluster of genes that encode for a family of proteins primarily excreted by the pancreas that are associated with islet regeneration (REG proteins encoded by REG1A, REG1B, REG3A, REG3G ), but are also expressed in the CNS and related to neurodevelopment in the fetal brain (de la Monte et al ., 1990) and neuronal sprouting and synaptogenesis in the adult brain (Acquatella-Tran Van Ba et al ., 2012). The associated variant was located in the pseudogene, REG1P, that was likely produced by a duplication event related to one of the primary genes in the cluster (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…A Manhattan plot for the two tailed tests is shown in Figure 1, and the top 20 results are displayed in Table 2. The most significant result emerged for a variant on chromosome 2 (rs879022, bp 79364463, p = 4.72e-09) located in a cluster of genes that encode for a family of proteins primarily excreted by the pancreas that are associated with islet regeneration (REG proteins encoded by REG1A, REG1B, REG3A, REG3G ), but are also expressed in the CNS and related to neurodevelopment in the fetal brain (de la Monte et al ., 1990) and neuronal sprouting and synaptogenesis in the adult brain (Acquatella-Tran Van Ba et al ., 2012). The associated variant was located in the pseudogene, REG1P, that was likely produced by a duplication event related to one of the primary genes in the cluster (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Its transient overexpression stimulates neurite outgrowth. The deposits of Reg-1α was found in the brain of very early stage Alzheimer disease patients and may reflect aberrant neuritic sprouting associated with synaptic disconnection and dementia (Acquatella-Tran Van Ba et al, 2012). Its putative receptor is ‘exostosin tumor-like 3′ protein encoded by the EXTL3 gene (decreased 2.396 fold at P7; Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…A homology search revealed that the cDNA was a homologue of a human multiple exostoses (EXT)-like gene, especially the human EXT-like gene 3 (EXTL3; over 97 % amino acid identity), indicating that the receptor was encoded by the EXTL3 gene and that it mediated growth signals of the Reg protein for β cell regeneration. After the report that the Extl3 gene encodes the Reg receptor [45], Acquatella-Tran Van Ba et al confirmed that Extl3 is a Reg receptor [46], and several groups also reported Extl3 as a Reg protein receptor [47][48][49][50][51]. In a later study, further advances in the Reg receptor (Extl3) were reported; Reg receptor (Extl3) overexpression in pancreatic β cells as well as Reg protein addition to β cells induced the activating transcription factor-2 (ATF-2) activation [52], and a β cell-specific knockout for Extl3 resulted in abnormal islet morphology with reduced β cell proliferation [53].…”
Section: Reg Receptormentioning
confidence: 90%
“…The Reg receptor (EXTL3) mRNA expression was also detected in the liver, heart, kidney, spleen, thymus, stomach, small intestine, and colon, as well as pancreatic acinar and ductal cells, suggesting that the Reg-Reg receptor system is involved with a variety of cell types in addition to β cells [29,30,[45][46][47][48][49].…”
Section: Reg Receptormentioning
confidence: 92%